Response to the Somali and Malian jihadist movements: What lessons for Mozambique? - Franco, A. C. S.; Ajú, M. M. (Revista Portuguesa de Ciência Política, 2022)
AbstractSince 2017, Mozambique’s Cabo Delgado province has witnessed an unprecedented level of violence attributed to jihadist movements. The security threat, instability and deteriorating humanitarian situation in the area has attracted the attention of regional and international actors. The aim of this article is twofold. On the one hand, it discusses the response to jihadist movements in Somalia and Mali in order to explain and contextualize external interventions in Mozambique. On the other hand, it explores the extent of lessons-learned based on the evidence from Somalia and Mali. Specifically, it considers how such interventions may help shade light towards a better understanding of the origin and evolution of Mozambican-based jihadist movement and the possible responses from external actors. The arguments are guided by a post-liberal approach. However, drawing from the relative deprivation theory, the article also focuses on the economic and social exclusion experienced in Cabo Delgado province and highlights the possible underlying root-causes of the current situation. As a main conclusion, lessons learned from stabilization and counterinsurgency interventions in Somalia and Mali must be an integral part of the responses to the Mozambique conflict. Keywords: external interventions; jihadist movements; Mali; Mozambique; post-liberal; Somalia